Improved control of nosocomial C. difficile transmission by daily use of an oxygen-releasing sporicidal disinfectant - Hell, Markus; Schmid, Daniela; Simons, Erica; Bernhofer, Christa; Voith, Martina; Wagner, Andrej; Salmhofer, Hermann; Achleitner, Dagmar; Stalzer, Patrik; Allerberger, Franz (International Journal of Infection Control, 2014)
Contaminated surfaces contribute to transmission of C. difficile in the healthcare setting. The aim of the investigation was to assess the effectiveness of an environmental disinfection protocol consisting of daily use of the oxygen-releasing sporocide Oxygenon® Liquid (Antiseptica) in preventing nosocomial CDI, compared to daily surface disinfection with a quaternary ammonium compound-based product plus the oxygen-releasing sporicide Perform® (Schülke+) for targeted sporicidal environmental disinfection. In a pre-post single group study with patients of two internal medicine wards (A and B) between February 2008 and May 2011, we compared the CDI rate between the pre- and post-intervention phase by calculating the post-pre phase CDI rate-difference and preventable fraction. In a pre-post parallel groups study from August 2009 until May 2011, the post-pre phase CDI rate-difference of the experimental group (internal medicine ward B) was compared with the post-pre CDI rate-difference of a control group (general surgery department) by calculating the between-group difference in the post-pre CDI rate-difference. In the pre-post single group study, among patients ≥ 70 year olds, the post-pre phase CDI rate reduction of 14.0/10,000 bed-days was significant, and preventable fraction of CDI was 60.2% (95%CI: 15.6%-82.8%). The results of the pre-post parallel groups study suggested a superiority of the new environmental disinfection protocol at borderline significance. The post-pre CDI rate-difference in the experimental group was greater than the post-pre rate-difference in the control group by 10.4/10,000 bed-days. Using a sporicide for daily surface decontamination may be superior to targeted sporicidal disinfection in preventing nosocomial transmission of C. difficile.